Pengaruh Financial Knowledge, Financial Attitude, dan Internal Locus of Control Terhadap Perilaku Manajemen Keuangan Generasi Z di Jakarta - Ester Lina Siringoringo; Lutfi Alhazami (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to empirically examine the influence of financial knowledge, financial attitudes, and internal locus of control on the financial management behavior of Generation Z in Jakarta. In today's fast-paced digital era, Generation Z faces increasingly complex challenges in managing personal finances. Despite having extensive access to financial information, many still lack a grasp of basic financial concepts. This gap in knowledge and attitudes can lead to unhealthy financial management behaviors, such as consumer debt and poor financial planning. Therefore, this study is important to provide insights into improving financial literacy and behavior among the younger generation. This study employed a quantitative approach with a survey method. Primary data were obtained through the distribution of questionnaires compiled using a Likert scale of 1-5. The population in this study was Generation Z in Jakarta aged 19–28 years and already earning an income. This population is very large and the exact number cannot be known in detail because it involves various occupational backgrounds, educational levels, and diverse economic conditions. Therefore, this study did not take the entire population, but only a representative portion through sample determination. The sampling technique used was purposive sampling, namely selecting respondents based on certain criteria in accordance with the research objectives. The number of samples used was 100 respondents, which was considered adequate and representative for analysis, so that the results of the study can describe the financial management behavior of Generation Z in Jakarta more accurately. Data analysis was performed using multiple linear regression with the help of SPSS software version 25. The results of the study indicate that financial knowledge has a positive and significant effect on the financial management behavior of Generation Z, meaning that the higher the financial knowledge, the better the financial management. Furthermore, financial attitude also has a positive and significant effect, indicating that a positive financial attitude encourages financial discipline and control. In addition, internal locus of control has been shown to have a positive and significant effect, so that Generation Z who believe in their own abilities tend to be more responsible in managing finances. Simultaneously, these three independent variables have a significant influence on the financial management behavior of Generation Z in Jakarta